Calm Christmas and a Happy New Year : a little book of festive joy - Kempton, Beth (New York : Scribner, 2020)
A delightful guide to a stress-free holiday season filled with mindfulness, joy, self-care, and festive magic. What if the month of December were soothing instead of stressful? Now you can celebrate a new kind of holiday season-one where you radiate calm and cultivate delight. Calm Christmas and a Happy New Year leads you out of the darkness of winter and back to the enchantment of an authentic and attainable Christmas season filled with merry gatherings, thoughtful gift-giving, and meaningful observations of annual traditions. Covering the time period from late November to early January, this joyful guide embraces all the festive holiday build-up and then welcomes the new year in a holistic, nurturing way. Author Beth Kempton gently encourages you to prioritize your holiday hopes and take a slower, more mindful approach to your celebrations. Kempton also offers helpful suggestions for making the most of winter, and recommends using this quiet time to dream new dreams, set goals, and aspire toward a beautiful year ahead. Filled with personal stories, tips, and advice for staying calm and connecting with others, Calm Christmas and a Happy New Year provides a cozy retreat from the pressure of striving for perfection. Instead of starting the New Year exhausted, in debt, and filled with regret, you will rejoice in the memories of the season feeling rested, rejuvenated, inspired, and calm.
Keywords: Christmas; Mindfulness (Psychology); Holidays -- Psychological aspects